Postural control and neuromuscular activation during balance in elite Chinese martial artists and sprinters - Zhu, Huanhuan; Wei, Xiaobin; Song, Qingquan; Zhao, Yifan; Chen, Hui; Chen, Xiaoping (Frontiers in Physiology, 2025)
BackgroundPostural control integrates core stability, coordination, and balance shaped by specific training. Sprinting emphasizes stretch–shortening-cycle power and trunk extensor use, whereas Chinese martial arts stress multi-planar core-hip control. Yet rigorous comparisons in elite athletes that pair functional performance with time-synchronized surface electromyography are scarce, limiting insight into how long-term training sculpts neuromuscular strategies when fundamental movement capacity appears similar. This study compares elite martial artists and sprinters to delineate differences in core stability, dynamic balance, explosive power, and task-specific muscle activation, informing conditioning and cross-training. Thirty-two first-level male athletes from Beijing Sport University (martial arts/sprinting, n = 16) participated in a cross-sectional study. Assessments included the Functional Movement Screen (FMS), Countermovement jump (CMJ), squat jump (SJ), and Y-Balance Test (YBT), administered in a Latin-square order. Surface Electromyography (sEMG) was collected from eight trunk and lower-limb muscles, normalized to maximum voluntary contraction. Jumps were segmented into pre-squat and extension phases, and YBT into squat and recovery phases. Statistical analyses employed normality and homogeneity tests, with independent-samples t-tests, Welch’s tests, or Mann–Whitney U tests as appropriate (α = 0.05).ResultsNo significant group differences emerged in overall FMS or YBT reach distances; however, martial artists scored higher on the Trunk Stability Push-up (p = 0.013). Sprinters achieved greater CMJ height and relative peak power (p < 0.05, d ≈ 0.83–0.87), whereas SJ outcomes did not differ. sEMG analysis showed higher rectus femoris and lateral gastrocnemius RMS and greater rectus abdominis iEMG (pre-squat) in martial artists, while sprinters exhibited higher erector spinae and gluteus maximus iEMG. During YBT, sprinters relied on rapid spinal extensor activation with partial gluteus medius compensation, whereas martial artists demonstrated integrated core–lower-limb coordination.ConclusionMartial artists and sprinters exhibit comparable functional movement and dynamic balance but diverge in core stability and neuromuscular strategies. Martial arts training enhances multiplanar core stability and coordinated muscle recruitment, while sprinting emphasizes stretch–shortening-cycle based explosive output and trunk extensor reliance. These findings provide evidence for targeted conditioning and potential crossdisciplinary training applications.